2004
DOI: 10.1002/app.20002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of highly oriented poly(γ‐benzylL‐glutamate) networks and gels with long channels with micrometer‐scale diameters

Abstract: Poly(␥-benzyl l-glutamate) (PBLG) gels with highly oriented ␣-helix chains were prepared by the crosslinking of PBLG chains through changes in the concentration of ethylenediamine, used as a crosslinker, in 1,4-dioxane in the presence of the strong magnetic field of an NMR magnet with a strength of 10.5 T. The experimental results showed that in one of these gels, long channels with an average diameter of about 100 m were formed by phase separation between crosslinked PBLG and the solvent. Furthermore, three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…BLG ratios (at least 24 : 76) prevent gelation entirely; however, the fact that P(BLG 0.89 -co-DLAG 0.11 ) 53 was able to gel shows that sufficiently low DLAG to BLG ratios (less than 24 : 76 and at least up to 11 : 89) does not prevent physical gelation. We also found that for similar LAG to BLG ratios, the α-helical contribution increases with increasing chain length.…”
Section: Paper Polymer Chemistrymentioning
confidence: 88%
See 2 more Smart Citations
“…BLG ratios (at least 24 : 76) prevent gelation entirely; however, the fact that P(BLG 0.89 -co-DLAG 0.11 ) 53 was able to gel shows that sufficiently low DLAG to BLG ratios (less than 24 : 76 and at least up to 11 : 89) does not prevent physical gelation. We also found that for similar LAG to BLG ratios, the α-helical contribution increases with increasing chain length.…”
Section: Paper Polymer Chemistrymentioning
confidence: 88%
“…Despite the harsh debenzylation conditions, the gels showed no collapse and maintained their overall shape and volume. ) showing an intense peak at 6-7°and a less intense peak at 17°(resolved by Levenberg-Marquardt curve-fitting); the amorphous halo is centered around 20-21°; (a) PBLG 51 , (b) P(BLG 0.76 -co-DLAG 0.24 ) 59 , (c) P(BLG 0.77 -co-LAG 0.23 ) 57 , (d) P(BLG 0.89 -co-DLAG 0.11 ) 53 . This indicates that the porous microstructure observed in the organogel was preserved, as confirmed by SEM (Fig.…”
Section: Mechanism Of Photo-crosslinking Gelationmentioning
confidence: 99%
See 1 more Smart Citation
“…These separations are attributed to the hexagonal lattice of the closed-packed structure of the rod-like a-helices: 11,18 the former separation is the longitudinal periodicity of the a-helices, and the latter one is similar to the reported transversal lattice constant of the hexagonal closed-packed structure of the a-helices. 9,11,29,30 The WAXD pattern for the nanofiber from the isotropic solution (D¼0.65 mm, Figure 7b) exhibited peaks slightly concentrated on the pole and the equator, which suggests a uniaxial orientation of a small fraction of the hexagonal lattice, whereas the pattern for the thicker aligned fiber electrospun from the isotropic solution (D¼1.35 mm) exhibited Debye-Scherrer rings (Supplementary Figure S1). This improvement in the orientation is consistent with the fiberdiameter dependence of Dn.…”
Section: Characterizationmentioning
confidence: 99%